2001
DOI: 10.1046/j.1365-2958.2001.02579.x
|View full text |Cite
|
Sign up to set email alerts
|

Fba, a novel fibronectin‐binding protein from Streptococcus pyogenes, promotes bacterial entry into epithelial cells, and the fba gene is positively transcribed under the Mga regulator

Abstract: In infection by Streptococcus pyogenes, fibronectin (Fn)‐binding proteins play important roles as adhesins and invasins. Here, we present a novel Fn‐binding protein of S. pyogenes that exhibits a low similarity to other Fn‐binding proteins reported. After searching the Oklahoma Streptococcal Genome Sequencing Database for open reading frames (ORFs) with an LPXTG motif, nine ORFs were found among those recognized as putative surface proteins, and one of them was designated as Fba. The fba gene was found in M ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(94 citation statements)
references
References 45 publications
4
90
0
Order By: Relevance
“…FbaA distributes broadly among streptococcal species, such as M1, 2, 4, 9, 13, 22, 28, etc. Moreover, it exhibits a high homology in different types of S. pyogenes (6). Recently, Terao et al reported that the immunogenic domains of FbaA were N terminus and PRR domain (10), and our recent data (not shown) showed the strongest immunogenic domain of FbaA was coiled-coil domain (CC) of the N terminus.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…FbaA distributes broadly among streptococcal species, such as M1, 2, 4, 9, 13, 22, 28, etc. Moreover, it exhibits a high homology in different types of S. pyogenes (6). Recently, Terao et al reported that the immunogenic domains of FbaA were N terminus and PRR domain (10), and our recent data (not shown) showed the strongest immunogenic domain of FbaA was coiled-coil domain (CC) of the N terminus.…”
Section: Discussionmentioning
confidence: 63%
“…Unfortunately, M protein is restricted as a vaccine candidate because it possesses multiple serotypes and often causes tissue crossreactions. A novel protein, FbaA, an Fn-binding protein expressed on the surface of GAS, was reported by Terao (6). Pandiripally et al confirmed the functions of FbaA in promoting entry of GAS into the cytoplasm of human epithelial cells through binding human complement regulatory proteins FH and factor H-like protein (FHL-1) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple in vitro studies have demonstrated that GAS isolates associated with invasive diseases efficiently invade epithelial cells (6,7). Although programmed cell death is an essential part of host defense against pathogens, it is considered that internalized GAS exploits this process to access the underlying sterile tissues (8,9).…”
mentioning
confidence: 99%
“…It is equipped with various surface-displayed and secreted virulence factors, such as M proteins, 31,32 Fba proteins, 33,34 C5a and SpeB, 35,36 and these proteins play a vital role in streptococcal colonization, invasion, dissemination and host damage. 37 GAS can survive and multiply in host cells, which requires suppression of host innate immunity.…”
Section: Discussionmentioning
confidence: 99%